Recovering lost customers - Радослав Сенић; Соња Милојевић (Mенаџмент у хотелијерству и туризму, 2015)
One of the most important tasks of tourism marketing, especially in hospitality and gastronomy sectors, is linked to establishing long term relationships with guests. Customers, in this case - guests, represent the most valuable assets of a company. Hotels can assure their survival, further growth and development through retaining the existing, attracting new and recovering lost guests. Keeping existing, loyal guests is the most lucrative business, attracting new guests is the most expensive one, whereas recovering of lost and often forgotten guests is a type of business that still has not received adequate attention. So far, marketing strategies have largely been focused onto the first two categories of guests. The focus of this paper is to examine defection of the existing and recovering lost guests. The paper reviews the life cycle of the relationship with customers and the significance of managing defected customers in it, the very process of managing customers return and reasons why customers have defected. The aim is to point to the importance of recovering lost customers (guests).